Advances in Supported Amine Adsorbents for Direct Air Capture of CO2 - Shakoor, Maryna; Battegazzore, Danianla (Journal of Green Energy and Environmental Engineering, 2026)
Amid escalating global climate change, carbon dioxide (CO2) direct air capture (DAC) technology has emerged as a critical solution for mitigating greenhouse gas emissions. Central to this technology are supported amine adsorbents, which have attracted considerable attention due to their unique properties and potential applications. However, these materials still face significant challenges, including limited adsorption capacity, insufficient selectivity, high costs, and inadequate long-term stability. This article provided a comprehensive review of recent advancements in supported amine adsorbents, focusing on three primary synthesis methods: impregnation, grafting, and in-situ polymerization. Impregnation, known for its simplicity and cost-effectiveness, is suitable for large-scale production but suffers from poor stability of the loaded amines. Grafting enhances amine stability through chemical bonding, yet its complex synthesis process and high costs hinder widespread adoption. In-situ polymerization, which enables uniform amine distribution via polymerization techniques, exhibits superior adsorption performance but remains technically challenging for industrial-scale applications. Furthermore, this review delved into the critical factors influencing adsorption performance, such as temperature, humidity, and carrier material properties, emphasizing that optimizing these parameters can significantly enhance adsorbent efficiency. Notably, in-situ polymerization adsorbents demonstrated exceptional potential for structural control, offering opportunities to improve both adsorption capacity and kinetics. Despite the promising prospects of supported amine DAC adsorbents, several challenges must be addressed to advance their practical application. This article proposed that future research should prioritize performance optimization and cost reduction, aiming to develop highly efficient, stable, and economically viable adsorbents. Additionally, interdisciplinary efforts are essential to explore novel carrier materials and innovative synthesis strategies, thereby providing robust theoretical and technical foundations for industrial deployment. Through sustained innovation and technological breakthroughs, supported amine DAC adsorbents are poised to play a pivotal role in achieving global sustainability goals and offering viable solutions to combat climate change.